2007
DOI: 10.1007/s10565-007-9033-y
|View full text |Cite
|
Sign up to set email alerts
|

Reduced alveolar macrophage migration induced by acute ambient particle (PM10) exposure

Abstract: Increased levels of particulate air pollution (PM10) have been implicated as a causal agent in pulmonary disease exacerbation and increased deaths from respiratory and cardiovascular disorders. The exact mechanism by which PM10 drives toxicity in the lung is still unknown, but studies have focused on inhibition of macrophage function and impaired alveolar clearance mechanisms. To assess the effects of PM10 on pulmonary macrophage clearance mechanisms ex vivo, Wistar rats were instilled with 125 or 250 microg o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 40 publications
2
11
1
1
Order By: Relevance
“…44 AMs have previously been shown to migrate toward complement component C5a. 28,45,46 We therefore chose the zymosan-activated FBS (a rich source of C5a) method to measure migratory capacity. We observed that the migratory capacity of AMs did not significantly change at 1 or 5 days after the 24-hour treatment with MWCNT-0.6 μm; however, at 1 and 5 days after treatment with MWCNT-20 μm, AM migratory capacity was markedly decreased.…”
Section: Discussionmentioning
confidence: 99%
“…44 AMs have previously been shown to migrate toward complement component C5a. 28,45,46 We therefore chose the zymosan-activated FBS (a rich source of C5a) method to measure migratory capacity. We observed that the migratory capacity of AMs did not significantly change at 1 or 5 days after the 24-hour treatment with MWCNT-0.6 μm; however, at 1 and 5 days after treatment with MWCNT-20 μm, AM migratory capacity was markedly decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Barlow and coworkers [54] assessed the effects of intratracheally instilled PM 10 collected from London on macrophage clearance in rats ex vivo . These authors concluded that acute PM 10 exposure has an effect on macrophage phagocytosis and chemotaxis that may be deleterious to particle clearance within the alveolar region of the lung.…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…En las ratas expuestas a ozono + CuSO 4 los macró-fagos presentaron además de vacuolas, pigmento en su citoplasma, lo que implicaría un mayor daño celular. Los macrófagos pigmentados se observan en la bronquiolitis respiratoria o del fumador, en tanto que en la proteinosis alveolar se detectan macrófagos vacuolados y pigmentados 28,29 .…”
Section: Discussionunclassified